Comments on Discussion Paper "Financial Instruments with Characteristics of Equity" (FICE) - TAN, Pearl Hock-Neo (Institutional Knowledge at Singapore Management University, 2018)
Comments are given on the Discussion Paper issued by the International Accounting Standards Board in June 2018 on Financial Instruments with Characteristics of Equity. The comments are given in response to the Board's public invitation for feedback on the Discussion Paper. The comments convey the author's concerns about the Discussion Paper's proposals in the light of the conceptual framework of financial reporting and a fundamental understanding of what equity and liability is. The comments propose approaches that the Board may consider in its subsequent development of its proposals.